Evaluating Digital Financial Apps for Accounting Education and Student Financial Literacy in Indonesia - Hasdik, Arif Rahman; Syukur, Mukarramah; Hartinah, Dwi Ayu Siti; Yus’an, Nurul Huda (Universitas Negeri Makassar, 2025)
This study aims to analyze the ten most popular digital financial applications in Indonesia and evaluate their potential use as learning media to support accounting education for university students. Employing a desk-review method with a descriptive–comparative approach, the research examines the functional features of each application using eight major criteria: ease of use, accuracy and completeness of transaction recording, availability of transaction history and financial reports, budgeting and financial planning tools, level of transaction detail, data export capabilities, security and privacy features, and the overall potential of each platform to facilitate accounting learning. The analysis integrates comparative scoring with qualitative assessment to highlight the strengths, weaknesses, and pedagogical value of each application across diverse user contexts. Results indicate that GoPay, DANA, and OCTO Mobile achieve the highest evaluation scores, demonstrating strong suitability for developing students’ financial literacy, reinforcing their understanding of accounting cycles, and enabling hands-on practice with real digital financial data. These applications provide features that align well with fundamental accounting competencies, such as classification, analysis, and interpretation of financial transactions. The study recommends incorporating selected digital financial applications into accounting curricula to enhance experiential learning, improve analytical and decision-making skills, and strengthen students’ readiness for modern digital financial environments.Penelitian ini bertujuan untuk menganalisis sepuluh aplikasi keuangan digital terpopuler di Indonesia serta mengevaluasi potensinya sebagai media pembelajaran untuk menunjang pendidikan akuntansi bagi mahasiswa. Dengan menggunakan metode desk review dan pendekatan deskriptif–komparatif, penelitian ini mengkaji fitur fungsional setiap aplikasi berdasarkan delapan kriteria utama: kemudahan penggunaan, akurasi dan kelengkapan pencatatan transaksi, ketersediaan riwayat transaksi dan laporan keuangan, fitur budgeting dan perencanaan keuangan, tingkat detail transaksi, kemampuan ekspor data, fitur keamanan dan privasi, serta potensi keseluruhan aplikasi dalam mendukung pembelajaran akuntansi. Analisis mengintegrasikan penilaian komparatif dengan kajian kualitatif untuk menyoroti kelebihan, kekurangan, dan nilai pedagogis masing-masing aplikasi dalam berbagai konteks penggunaan. Hasil penelitian menunjukkan bahwa GoPay, DANA, dan OCTO Mobile memperoleh skor evaluasi tertinggi, sehingga memiliki tingkat kesesuaian yang kuat untuk meningkatkan literasi keuangan mahasiswa, memperkuat pemahaman siklus akuntansi, dan memberikan pengalaman praktik langsung menggunakan data keuangan digital nyata. Aplikasi-aplikasi tersebut menyediakan fitur yang selaras dengan kompetensi dasar akuntansi, seperti klasifikasi, analisis, dan interpretasi transaksi keuangan. Penelitian ini merekomendasikan integrasi aplikasi keuangan digital tertentu ke dalam kurikulum akuntansi untuk meningkatkan pembelajaran berbasis pengalaman, memperkuat kemampuan analitis dan pengambilan keputusan, serta meningkatkan kesiapan mahasiswa dalam menghadapi lingkungan keuangan digital modern.